Breast asymmetry as mammographic finding of breast carcinoma: a case series - Hassan, Radhiana; Abdul Rashid, Mohd Amran; Yahaya, Azura Sharena; Muhammed Nordin, Ellyda (2011)
Asymmetric breast tissue has been reported to be depicted on 3% of mammograms and is nearly always benign. Asymmetric breast might be due to a normal variation, postoperative changes or hormonal replacement therapy. However, it may also indicate an underlying breast cancer, especially with a focal asymmetric density that corresponds to a palpable lesion. Adequate clinical information and supplementary imaging studies may help to interpret and manage asymmetric breast findings.